Management of True Gastroduodenal Artery Aneurysm: A Case Report and Literature Review - Siju T Abraham; Siddharth Matad; Vinay Philip Nazareth; Sumanth Raj; Vivek Anand (Indian Journal of Vascular and Endovascular Surgery, 2024)
Gastroduodenal artery (GDA) aneurysms are rare forms of splanchnic artery aneurysms with varied etiopathogenesis. Mostly found incidentally, early identification with advanced imaging tools and timely intervention of these aneurysms are essential due to the associated high risk of rupture, morbidity, and mortality with GDA aneurysms. We report a case of successfully treated GDA aneurysm using endovascular coil embolization.